Indexation of dynamic and static geomechanical properties of a cemented aggregate for transportation engineering - António Joaquim Pereira Viana Da Fonseca (2014)
This paper presents an extensive experimental program aiming to the mechanical characterisation of an aggregate stabilised with cement. This geomaterial is the product of a quarry of limestone located in north region of Portugal. The aggregate is often used in current subgrading of infrastructures for transportation, namely in railway lines. Complementary, aggregate-cement admixtures are used for transition zones, such as in between deformable embankments on soft grounds lining on rigid structures, such as bridges founded on deep foundations, such as piles or similar. The demand for smooth transition between diverse stiffness zones implies an optimization of the composition of the enriched materials that will be used for such purpose, such as aggregate-cement admixtures. The optimization requires a thorough mechanical characterisation including dynamic tests, with recourse to geophysical techniques, cyclic and monotonic triaxial tests and, ideally, indexed to simple uniaxial compression and indirect tensile tests. The results that will be presented herein have allowed a good mechanical characterisation of the referred aggregate, in terms of the estimation of combinations of the cement content and the admixture compaction level, resulting in new correlations for design purposes.